Reportażowe reprezentacje pamięci w tomie Michała Olszewskiego „Najlepsze buty na świecie” - Piechota, Magdalena (Stylistyka, 2019)
The article analyses how reportage creates representations of individual and shared memories as well as official and private memories, as described by Michał Olszewski in his volume “The Best Shoes in the World”. Another topic covered in the book and investigated in this article is the mechanisms of memory repression brought about by events of the Second World War. The most important topics and problems incorporated in Olszewski’s book are the erosion of memories of experiences during and after the war; the reasons for, and mechanisms of, this erosion; self-reflection on how memories determine our heritage; and the hiding and falsification of historical facts such as greed and collaboration. An important element of Olszewski’s narrative is how the past is commercialised in performances by reconstruction groups.